Comprehension Effects of Connectives Across Texts, Readers, and Coherence Relations. Issue 5 (4th July 2019) - Kleijn, Suzanne; Pander Maat, Henk L.W.; Sanders, Ted J.M.
ABSTRACT: Studies investigating the effect of connectives on comprehension have yielded different results, most likely because of differences in methodology and limited samples of texts and readers. We added and removed causal, temporal, contrastive, and additive connectives in 20 authentic Dutch texts. Dutch adolescents (n = 794) differing in reading proficiency filled out four "HyTeC" cloze tests. Connectives were found to affect comprehension on a local level but not on a global level. However, a post-hoc analysis revealed a global comprehension effect for difficult texts but not for easy texts. Local effects were predominantly carried by the difficult texts as well. The direction of the effect did not vary between reading proficiency or readers' educational level but did vary between types of coherence relations. Contrastive and causal connectives increased comprehension, whereas additive connectives reduced comprehension. Our large-scale study shows that effects of connectives on text comprehension are consistent between readers but not between texts and types of coherence relations.